470 Feasibility of an community mobilisation intervention to prevent childhood injuries in Bangladesh. (20th November 2022) - Bidgoli, Hassan Haghparast; Ahmed, Ashraf Uddin; Kuddus, Abdul; Sondaal, Annemijn; Rosato, Mikey; Morrison, Joanna; Tasmin Nahar, MRS; Rahman, Fazlur; Hasselberg, Marie; Fottrell, Edward; Azad, Kishwar
Abstract : Unintentional injuries are among the leading causes of childhood deaths, with 90% of injury-related deaths occurring in low- and middle-income countries (LMICs). In Bangladesh, more than 40% of childhood deaths are due to injuries, with drowning responsible for over 90% of these. In order to fill the evidence gap on the effective and cost-effective interventions in LMICs, we developed and assessed the feasibility and acceptability of an integrated package of community mobilisation interventions in preventing injuries among under 5 children in rural Faridpur, Bangladesh during 2021–2022. The intervention package comprises of three components: 1) participatory community groups using participatory learning and action cycle to identify and address risk factors for unintentional injuries in their communities; 2) mhealth messages to generate awareness on unintentional injury risk factors and prevention strategies and, 3) household visits to provide tailored advice on reduction of injury hazards in the home environment. The intervention builds on our successful experience of participatory community groups in resource constrained settings, including Bangladesh, in improving maternal and newborn survival and diabetes prevention. The intervention was co-developed through engagement with different stakeholders, and piloted for 6 months in two villages in Faridpur district. Evaluation of the pilot implementation is being finalised and its findings will be presented at the conference. We used MRC guide to process evaluation for complex intervention as the main theoretical framework to evaluate pilot testing of intervention, as well as drawing on implementation research outcomes variables.